A Conceptual Model of Tourist Motivation, Tourist Satisfaction and Destination Loyalty - Mahadzirah, Mohamad; Mutia Sobihah, Abd Halim; Nor Azman, Mat Ali @ Salim; Zainudin, Awang; Loganathan, Nanthakumar; Nur Izzati, Ab Ghani (2015)
A study on push and pull motivation recently has been primarily used to examine the leisure travel motivation for measuring tourist behaviour. Previous studies found that there were significant relationship among push and pull motivation, tourist satisfaction and destination loyalty. However, the intersection between these fields is relatively explored. The purpose of this study is to propose a conceptual model that examine the relationship among push and pull motivation, tourists’ satisfaction and destination loyalty in the Malaysia Tourism context. The data will be collected at the Sultan Mahmud Airport at the departure hall using self-administered questionnaire. This study will use Exploratory Factor Analysis (EFA) to reduce the number of variables in both push and pull motivation, Confirmatory Factor Analysis (CFA) to confirm the items derive from EFA and Structural Equation Modelling (SEM) to examine the relationship among push and pull motivation, tourist satisfaction and destination loyalty. The findings of this study would provide insightful to the Malaysia Tourism Board by understanding tourists’ motivations as it can improve tourist satisfaction. This is because tourists who are satisfied with the destination they had visited will probably recommend to their friends and relatives and have intention to visit that particular place again.